Тимур и его команда: [роман и повести] / А. П. Гайдар - Гайдар Аркадий Петрович (Серия "Внеклассное чтение", 2008)
Экземпляры: М/а ДБ (20091007) / Инвентарный номер: 94990 / Цена: 73.20 / Авт.знак: Г 14 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6